The effect of high-intensity training and detraining on FOXO3a/MuRF1 and MAFbx levels in soleus muscle of male rats - shahin sheibani; farhad daryanoosh; mohsen salesi; maryam koushkie jahromi; nader tanideh (فصلنامه ابن سینا)
Background Inactivity may result in loss of muscle volume and subsequently reduce the power, by activating proteasome signaling pathways, which leads to a decrease in quality and expectations of life. The aim of this study was to evaluate the effect of high-intensity training and also detraining on the signaling pathways of FOXO3a, MAFbx, and MuRF1. Materials and methods: In this study, 32 2-month male Sprague-Dawley rats were used. At first, periodic exercise with intensity of 85-100% VO2max was performed for six weeks. Then, the groups (detrained for 48h, 7w, and 14w) were detrained and then soleus muscle was removed from hind limb. H&E staining and histochemical procedure were used to measure the amount and percentage of skeletal muscle fibers type. Also, RT-PCR method was used to examine gene changes. Results: The mean weight of the soleus muscle increased after exercise and decreased significantly after detraining (p=0.001).The fiber type conversion were happened from I to IIA (p=0.001). Hypertrophy was observed in fibers after training, whereas atrophy was seen after detraining in type II fibers (p=0.001). FOXO3a and MAFbx levels were significantly increased after training and decreased after detraining period (p=0.001).The MuRF1 expression shown an increase and a decrease after training and detraining, respectively (p=0.001). Conclusion: The results of this study indicated that the exercise couldn’t prevent atrophy during the period of detraining. Also, the activation of pathway FOXO3a/MAFbx, not the FOXO3a/ MuRF1, is the atrophy inducer during detraining. In this regard, probably MuRF1 is an indirect target of FOXO3a and cannot always be an appropriate marker of atrophy. MuRF1 probably plays a more important role in pathological atrophy conditions.